Digital close range photogrammetry : calibration of different digital sensor using different test field and application - Anuar Ahmad 613407; Ibrahim Busu 249973; Ghazali Desa 195029; International Symposium and Exhibition on Geoinformation (2003 : Shah Alam, Selangor) 474407 (Skudai : Universiti Teknologi Malaysia, 2003)
27